Concepções, crenças e competências referentes à leitura, reveladas por professores(as) de Matemática e o desenvolvimento de práticas de leitura em suas aulas - Oliveira, Emilio Celso de (2007)
The objective of this dissertation is to investigate conceptions, beliefs and skills relevant to reading that are revealed by Mathematics teachers, plus the development of reading practices in their classes, having in view that text reading & writing has started to figure as a task that should be shared by teachers from different areas of knowledge. Initially I have sought to bring theoretical contributions by reviewing the bibliography in order to place the question of reading under both individual and collective perspectives, as well as to define the notion of reading competence and skills, and to clarify what is understood by beliefs and conceptions in educational literature. Through such desk research I have identified, in documents produced by state and municipal educational systems, the main methodological recommendations regarding the development of reading competence. The field research outlined the reading profile of groups of Maths teachers in state and municipal school systems, identified their conceptions and beliefs in regard to reading competences, and highlighted reading practices in their classes. The research confirms the importance of a commitment shared by all areas of knowledge as regards the learning of how to read and write, and it underlines that Mathematics knowledge acquisition passes through specific genres of text, and it falls to the teacher to teach students how to read them. One result is that the methodology of problem resolution designed by Polya allows for a Mathematics teacher to explore reading and writing skills preconized by Solé. I have concluded that in state and municipal public school systems, because there is a great number of schools it is possible to detect a difficulty for official texts to circulate, the implication of which is a fragmented reception of information about educational policies and methodological recommendations. Our research suggests the relevance in both initial and continued education of Mathematics teachers, of the introduction of studies on text reading & writing, so that teachers will in the future develop reading & writing practices in their classes